Penguatan Kompetensi dan Keterampilan Guru Madrasah Se-Kota Semarang dalam Mengembangkan â€œWeb Based Assesmentâ€ Menggunakan Schoology - Arsini, Arsini (LP2M of Institute for Research and Community Services - UIN Walisongo, 2017)
This devotion aims to madrasah teachers in the city of Semarang able to develop web based assessment and able to improve the quality of process and learning outcomes. Devotion is done by providing training and assistance of web-based automated assessment (web based assessment) to madrasah teachers in Semarang city. The training was conducted in Physics Computational Laboratory of Physics Department of UIN Walisongo Semarang. Web-based automated assessment exercises (web basedassesment) are conducted using schoology. The result of this program of devotion is the training activity of making web basedassesment has been able to increase the competence and teachers of madrasah aliyah in Semarang city and develop web based automatic assessment in madrasah. Secondly, through teacher training activities can improve the ability in developing online learning media as an independent learning media for students. Â Teachers who have received training are expected to pass on their knowledge to teachers in their respective schools.Â Pengabdian ini bertujuan agar guru-guru madrasah di kota Semarang mampu mengembangkan web based assesment serta mampu meningkatkan kualitas proses dan hasil pembelajaran. Pengabdian dilakukan dengan mengadakan pelatihan dan pendampingan penilaian otomatis berbasis web (web based assesment) kepada guru-guru madrasah se kota Semarang. Pelatihan dilaksanakan di laboratorium Fisika komputasi Jurusan Fisika UIN Walisongo Semarang. Pelatihan penilaian otomatis berbasis web (web basedassesment) dilaksanakan dengan menggunakan schoology. Hasil dari program pengabdian ini adalah kegiatan pelatihan pembuatan web basedassesment telah mampu meningkatkan kompetensi dan guru-guru madrasah aliyah di kota Semarang dan mengembangkan penilaian otomatis berbasis web di madrasah. Kedua, melalui kegiatan Pelatihan guru mampu meningkatkan kemampuan dalam mengembangkan media pembelajaran online sebagai media pembelajaran mandiri bagi siswa. Guru yang telah mendapatkan pelatihan diharapkan dapat menularkan ilmunya kepada para guru di sekolah masing-masing.